2018
DOI: 10.1186/s13059-018-1503-4
|View full text |Cite
|
Sign up to set email alerts
|

A simple genetic basis of adaptation to a novel thermal environment results in complex metabolic rewiring in Drosophila

Abstract: BackgroundPopulation genetic theory predicts that rapid adaptation is largely driven by complex traits encoded by many loci of small effect. Because large-effect loci are quickly fixed in natural populations, they should not contribute much to rapid adaptation.ResultsTo investigate the genetic architecture of thermal adaptation — a highly complex trait — we performed experimental evolution on a natural Drosophila simulans population. Transcriptome and respiration measurements reveal extensive metabolic rewirin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 80 publications
3
114
4
Order By: Relevance
“…While the mean observed selection coefficient depends strongly on the minimum threshold applied to infer selected SNPs, which makes comparisons among studies using different thresholds difficult, the maximal s per REA observed here exceeded those reported for haplotypes in similar studies on Drosophila (Barghi et al, ). This may be the result of the higher number of starting haplotypes (800) and a higher N e in the replicates throughout the experiment (factor 2–4) compared to previous E&R studies with Drosophila (Barghi et al, ; Mallard, Nolte, Tobler, Kapun, & Schlötterer, ; Tobler et al, ), allowing for efficient selection of favourable variants.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While the mean observed selection coefficient depends strongly on the minimum threshold applied to infer selected SNPs, which makes comparisons among studies using different thresholds difficult, the maximal s per REA observed here exceeded those reported for haplotypes in similar studies on Drosophila (Barghi et al, ). This may be the result of the higher number of starting haplotypes (800) and a higher N e in the replicates throughout the experiment (factor 2–4) compared to previous E&R studies with Drosophila (Barghi et al, ; Mallard, Nolte, Tobler, Kapun, & Schlötterer, ; Tobler et al, ), allowing for efficient selection of favourable variants.…”
Section: Discussionmentioning
confidence: 96%
“…This may be the result of the higher number of starting haplotypes (800) and a higher N e in the replicates throughout the experiment (factor 2-4) compared to previous E&R studies with Drosophila (Barghi et al, 2019;Mallard, Nolte, Tobler, Kapun, & Schlötterer, 2018;Tobler et al, 2013), allowing for efficient selection of favourable variants.…”
Section: Pervasive Common Genomic Adaptation Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing haplovalidate, which reconstructs selected haplotype blocks from genomic E&R time-series data, we provide a tool, to make the reconstruction of selected haplotypes a routine method that does not rely on the availability of haplotype information, neither from the founder population, nor from evolved individuals. Haplovalidate can be applied to a broad range of data, including few selection targets (Mallard et al, 2018) as well as many .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic rewiring is a common response among different organisms to their surrounding environment 1 . Different cell types differ in their preferred mode of metabolism in order to harness energy and generate its required set of metabolites 25 .…”
mentioning
confidence: 99%